Spatiotemporal variations of bacterial communities and functional genes in the water and sediments of a typical river influenced by reservoir operations - Wen, Jie; Liu, Shanshan; Wang, Yuchun; Khan, Mohd Yawar Ali; Zhou, Xuejian; Li, Shanze; Bao, Yufei; Cui, Xiaoyu; Huang, Zhihua; Sun, Meng; He, Hanxiao (Frontiers in Environmental Science, 2025)
IntroductionMicroorganisms are essential for cycling phosphorus and nitrogen and play a crucial role in maintaining the health and stability of river ecosystems. The reservoir operation changes the river's hydrological processes, forming reservoir inundation areas and influencing the diversity of microorganisms and their environmental functions.MethodsTo study the microbial composition and action mechanism in rivers affected by reservoir operation, Xiangxi River, the closest tributary to the Three Gorges Dam on the Yangtze River, was sampled to examine the spatiotemporal fluctuations of bacterial populations and functional genes in water and sediments. The physicochemical properties, microbial communities and functional genes were analyzed in August 2022 and June 2023.ResultsSpatially, except for conductivity, the chlorophyll (Chl), dissolved oxygen (DO), and pH values in the upper reaches of the basin were higher than those in the mouth (where it joins the Yangtze River). Specific physicochemical gradients created by the reservoir operation drove spatial and temporal shifts in bacterial community structure. In water samples (W), dominant microbial species included Exiguobacterium and Candidatus Fonsibacter, contributing to organic matter degradation and nutrient transformation. Nitrospira indicated their roles as nitrifiers or denitrifiers in sediment samples (S), essential for nitrogen cycling. In the mouth zone, Methyloceanibacter dominated in the transition zone, and they were involved in methane or organic metabolism.DiscussionThe dominance of Microcystis in the upstream region reflected its prevalence in nutrient-rich, algal-rich environments. Paralia in the middle of the river highlighted the favorable conditions of suitable light and moderate flow rates for diatom growth. Reservoir regulation also altered the functional gene composition, making it more similar to that found in lake ecosystems. The most abundant functional genes were those associated with Amino Acid Transport and Metabolism, while phosphorus-related genes predominantly involved energy production and conversion. The dominance of genes linked to electron transport underscored the pivotal role of microbial respiration and oxidative phosphorylation in energy metabolism, which was fundamental to ecosystem productivity.